The Influence of Sugar-Processing Effects on Water in Treatment Plants. (2016) - Morar, Florica; Rus, Dana; Lung, Bogdan-Ionut
Abstract: The present paper is a study regarding the influence of waters resulted from the production of sugar from sugar beet on waters in wastewater treatment plants. The objective of the paper is to prove that wastes, especially organic ones, resulted from the production of sugar from sugar beet ( Beta vulgaris L .) may have a significant effect on the quality of water entering or leaving water treatment plants, unless appropriate measures are taken to pre-treat and/or treat wastewater. That is why the existence of norms, standards and/or instructions establishing the qualitative conditions of water, on different lines or technological flows, is particularly important for the policies regarding the economical use of water resources. The fact that the capacity of the wastewater treatment station in Ludus is below the designed level, the sometimes inadequate separation of vegetable wastes from sugar beet root before processing lead to the exceedance of the accepted value for some water quality indices (total suspensions, CCOCr ), especially during the campaign periods.